Use of point-of-care ultrasound in the management of pediatric patients with severe scorpion sting - Sartorelo Almeida, Juliana; de Paiva Oliveira, Larissa; Rodrigues Santos, Jayne (LAJEC - Latin American Journal of Emergency Care, 2024)
Scorpion stings are the leading cause of animal envenomation in Brazil, and children are the most vulnerable group to complications. This is the case report of a 6-year-old patient who developed cardiogenic shock after a severe scorpion sting. In the patient’s diagnostic and therapeutic approach, the use of point-of-care ultrasound optimized the time taken to administer medication, helped with the necessary invasive procedures and promoted immediate assessment after the therapies had been instituted, in each phase of the approach. The aim of this report was to demonstrate the importance of this tool in the clinical assessment of patients with signs of severe scorpionism in the emergency department.